Implozja (nowej) prozy - Pasterska, Jolanta (Tematy i Konteksty, 2015)
It is a fact that, since the turning point of 1989, there has been a discussion on the face of new prose. A specialist in literature, a critic and a reader face two main questions: what kind of prose it is and how to read it. In the long term, in turn, questions concerning the ‘trend’ and the quest for new prose arise. In order to attempt to answer these questions, one needs to pay attention to the causes and source/sources of the changes which can be found ‘outside’ the literature, and which are related to cultural, psychological, social and sociological transpositions. It is also important to determine the degree and direction of writing dependent on them. The authors of the papers gathered in this volume have portrayed a wide panorama of new prose and paid attention to both promising and less sparkling debuts. They have focused on the transformations of Polish prose, its aesthetic, ethical and cognitive values.